2014
DOI: 10.1016/j.molcel.2014.02.015
|View full text |Cite
|
Sign up to set email alerts
|

SAICAR Induces Protein Kinase Activity of PKM2 that Is Necessary for Sustained Proliferative Signaling of Cancer Cells

Abstract: Abnormal metabolism and sustained proliferation are hallmarks of cancer. Pyruvate kinase M2 (PKM2) is a metabolic enzyme that plays important roles in both processes. Recently, PKM2 was shown to have protein kinase activity phosphorylating histone H3 and promoting cancer cell proliferation. However, the mechanism and extent of this novel protein kinase in cancer cells remain unclear. Here, we report that binding of SAICAR, a metabolite abundant in proliferating cells, induces PKM2’s protein kinase activity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
170
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(176 citation statements)
references
References 33 publications
6
170
0
Order By: Relevance
“…5 Interestingly, the interaction exists in several cases, indicating that PKM2 may also play a role in regulating DNA damage signaling in the context of a transcriptional inactivated P53.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Interestingly, the interaction exists in several cases, indicating that PKM2 may also play a role in regulating DNA damage signaling in the context of a transcriptional inactivated P53.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, non-metabolic function of PKM2, which is mainly associated with the nuclear PKM2, has been identified as a major contributor during tumorigenesis. For example, nuclear PKM2 displays kinase activity in phosphorylating a number of protein substrates, including histone H3 (4,5), signal transducer and activator of transcription 3 (stat3) (6,7), Bub3 (8), and myosin light chain 2 (MLC2) (9), for which PKM2 uses the high-energy phosphate from PEP but not ATP as a phosphate donor. The PKM2-induced phosphorylations of stat3 at tyrosine 705 and histone H3 at threonine 11 respectively activate the transcriptions of MEK5 and endothelial growth factor (EGF)-stimulated cyclin D1, leading to increased tumor cell proliferation.…”
mentioning
confidence: 99%
“…The role of PKM2 as a pleiotropic protein kinase has been demonstrated by protein microarray experiments, which found that more than 100 human proteins, mostly protein kinases, are phosphorylated by PKM2. In particular, PKM2 phosphorylates and activates ERK1/2, and the sustained ERK1/2 activation mediated by PKM2 is instrumental for cell proliferation (Keller et al, 2014). PKM2 has also been shown to interact with Oct4 (also known as POU5F1) upon treatment with dichloroacetate, a pyruvate dehydrogenase kinase inhibitor that promotes mitochondrial oxidative phosphorylation (Morfouace et al, 2014).…”
Section: Non-metabolic Functions Of Pkm2mentioning
confidence: 99%
“…Increased PK activity through small molecule activation of PKM2 also impairs tumor growth in mice (Anastasiou et al 2012). Furthermore, potential nonglycolytic functions of PKM2 have been proposed (Luo et al 2011;Yang et al 2011Yang et al , 2012aGao et al 2012;Lu 2012;Keller et al 2014) but are controversial (Hosios et al 2015). Despite numerous studies of PKM2 in cultured tumor cells, whether PKM2 is required for cell proliferation in vivo remains a topic of debate.…”
mentioning
confidence: 99%